Pola IKM dan UMKM di Bali - Afifahtus Syaleha; Muhammad Yasin (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Industry is an economic sector that uses machines and labor to produce goods or services. Manufacturing, mining, construction, energy, and technology are some of the industry subsectors. Each subsector has an important role in economic growth and development of the country. Industry plays an important role in meeting society's needs, creating jobs, increasing national income, and encouraging innovation. Small and Medium Industries (IKM) consist of small and medium enterprises operating in various sectors. SMEs make an important contribution in creating jobs, local economic growth and national industrial development. The government has paid great attention to the development of MSMEs through various programs and policies, as well as support from the private sector and financial institutions.